Communicative Language Teaching for Elementary Students Speaking Skill Development: Pengajaran Bahasa Komunikatif untuk Siswa Sekolah Dasar Pengembangan Keterampilan Berbicara - febrianti masrum bidhiana; Ahmad Nurefendi Fradana (Academia Open, 2025)
General Background: Speaking skill constitutes a central component of Indonesian language learning in elementary education as it supports students’ confidence, interaction, and meaningful communication. Specific Background: Classroom observations revealed that many students remained passive and hesitant to express ideas orally despite existing instructional strategies. Knowledge Gap: Prior studies mostly emphasized isolated techniques or regional language contexts, with limited examination of communicative approaches in Indonesian language classrooms at the elementary level. Aims: This study analyzes supporting and inhibiting factors in implementing Communicative Language Teaching and evaluates its role in developing students’ speaking abilities. Results: Using a descriptive qualitative design with observation, interviews, and documentation, findings show increased student participation, courage, fluency, and appropriate intonation. Teacher creativity, varied learning media, contextual materials, and positive feedback acted as key supports, while limited time, low confidence, and uneven participation emerged as barriers. Novelty: The study provides a contextual analysis of classroom-based communicative practices combined with identification of practical enablers and constraints. Implications: The findings recommend interactive tasks, group discussions, and contextual media integration to foster communicative competence and active engagement in elementary language instruction. Keywords: Communicative Language Teaching, Speaking Skills, Elementary Education, Indonesian Language Learning, Classroom Interaction Key Findings Highlights: Learners displayed greater oral participation and confidence during tasks Contextual materials and varied media supported active engagement Psychological barriers and time constraints limited equal involvement